Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s12199-012-0315-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lifestyle and lifestyle-related factors in a rural–urban population of Japan

Abstract: Objective To clarify the actual state of residents' lifestyle in a mixed rural-urban area in Japan, and to investigate the relationship between residents' lifestyle and lifestyle-related factors. Methods The Japanese version of Health Promoting Lifestyle Profile-II (HPLP-II), lifestyle-related factors developed through group work with residents of Town A, and demographic variables were used to evaluate 1176 community residents' lifestyles and associated factors. Results Factor analysis revealed that there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Findings from the current study suggested that factors influencing the HPLP-II scores included gender, age, occupation, and family income. These factors are consistent with findings from other studies [ 25 , 26 , 34 ]. But for each domain, their influencing factors might vary depending on where the studies were conducted.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Findings from the current study suggested that factors influencing the HPLP-II scores included gender, age, occupation, and family income. These factors are consistent with findings from other studies [ 25 , 26 , 34 ]. But for each domain, their influencing factors might vary depending on where the studies were conducted.…”
Section: Discussionsupporting
confidence: 93%
“…Among the six subscales of HPLP-II, the highest subscale score is interpersonal relations, and the lowest subscale score is physical activity. This is similar with the results from other countries [ 26 , 34 – 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…World health organization (WHO) point out over 53% of deaths around the world were caused by adverse behavioral lifestyles [ 6 ]. Some chronic diseases were known as behavior-related diseases, such as the occurrence of hypertension is closely associated with poor health-promoting-lifestyles [ 7 ]. And due to the unhealthy lifestyles, increased prevalence of physical disorders, nursing shortage, low income, and social isolation, older adults would feel lonely and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the small sample sizes ( n = 10 in each group), the scores on the overall HPLP-II in both groups were within the ranges obtaining in 512 male residents (mean age 45.5 ± 13.1 years) in a mixed rural-urban representative area in Japan. The actual states of the community residents’ ( n = 1176: 512 males and 664 females) lifestyles were recently investigated using the same HPLP II questionnaires used in this study [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HPLP was originally developed by Walker, Sechrist, and Pender in 1987 and revised as HPLP-II in 1995 [ 23 ]. Wei et al developed the Japanese version of the HPLP-II and established its validity and credibility with a Cronbach’s α internal consistency coefficient of 0.90 [ 24 ]. The HPLP-II is a 52-item questionnaire composed of two main categories and six sub-dimension scales.…”
Section: Methodsmentioning
confidence: 99%